Health workers' perspectives on implementation of an integrated medical male circumcision strategy in KwaZulu-Natal, South Africa - Rogerio Phili (AOSIS, 2014)
Background: KwaZulu-Natal province began implementation of voluntary medical male circumcision (VMMC) as an integral part of its HIV infection prevention strategy that includes other programmes such as HIV counselling and testing (HCT), screening and treatment of sexually transmitted infections and tuberculosis, and other sexual and reproductive health services. This followed randomised controlled trials that showed up to 60% HIV infection risk reduction amongst circumcised men. Implementation of the strategy occurred despite absence of knowledge of operational barriers and its acceptability to health care workers (HCWs). Objectives: The study aimed to explore HCWs' perspectives of and barriers to strategy implementation at public sector health facilities to inform implementation policy. Method: A purposive quota sampling method was used to select HCWs for focus group discussions at three study sites. Participants were asked open-ended questions using an interview schedule based on a literature review to explore acceptability of and perceptions regarding provision of the strategy. Thematic analysis was conducted. Results: Acceptability of the strategy was high amongst the participants; however, there was limited knowledge of some key concepts of the strategy, personnel role confusion, missed opportunities for client recruitment, and infrastructural constraints. Negative perceptions included beliefs that VMMC would discourage condom use and cause stigma associated with non-circumcision of HIV-positive males, with perceptions of sexual behavioural disinhibition in circumcised men. Conclusion: There is a need to engage further with stakeholders if implementation of VMMC is to be successful. More training and support needs to be provided to HCWs at public sector facilities. Agtergrond: Die implementering van vrywillige mediese manlike besnyding (VMMC) is 'n integrale deel van KwaZulu-Natal provinsie se MIV-voorkomingstrategie, wat ander programme soos MIV-berading, siftingstoetse (HCT) en die behandeling van seksuele oordraagbare siektes (STI), asook ander seksuele en reproduksie-gesondheidsdienste (geïntegreerde VMMC) insluit. Dit volg op die resultate van ewekansige gekontroleerde steekproewe wat 'n doeltreffendheid getoon het van tot 60% vermindering in HIV-risiko onder mans wat besny is. Die implementering van die strategie het plaasgevind ten spyte van die afwesigheid van kennis van operasionele struikelblokke of aanvaarding deur gesondheidswerkers (HCWs). Doelwitte: Die studie is daarop gerig om HCW se perspektiewe en hindernisse vir die implementering van die VMMC program by die openbare sektor se gesondheidsfasiliteite te verken, ten einde die uitvoering van die beleid vas te stel. Metode: Die doelgerigte kwotasteekproefmetode is gebruik om HCW deelnemers vir fokusgroepbesprekings (FGDs) op drie studieterreine te kies. Deelnemers is oop vrae gevra met behulp van 'n onderhoudskedule gebaseer op 'n literatuuroorsig van die aanvaarbaarheid en persepsies aangaande die voorsiening van die strategie. Tematiese analise is in ooreenstemming met die doelwitte van die studie gedoen. Resultate: Die aanvaarbaarheid van VMMC was hoog onder die deelnemers, maar 'n paar probleemareas is geïdentifieer: beperkte kennis van belangrike begrippe van die strategie, personeelrolverwarring, geleenthede vir kliëntwerwing en infrastruktuurbeperkings. Negatiewe persepsies het ingesluit: oortuigings dat VMMC die gebruik van kondome sou voorkom, die stigma wat verband hou met onbesnede HIV-positiewe mans en die persepsie van onderdrukte seksuele gedrag by mans wat besny is.